Promoting chemical laboratory safety and security in developing countries (National Research Council, 2010)
"There is growing concern about the possible use of toxic industrial chemicals or other hazardous chemicals by those seeking to perpetrate acts of terrorism. The U.S. Chemical Security Engagement Program (CSP), funded by the U.S. Department of State and run by Sandia National Laboratories, seeks to develop and facilitate cooperative international activities that promote best practices in chemical security and safe management of toxic chemicals, including: partnering with host governments, chemical professionals, and industry to assess and fill gaps in chemical security abroad; providing technical expertise and training to improve best practices in security and safety among chemical professionals and industry; increasing transparency and accountability for dangerous chemical materials, expertise, and technologies; and providing opportunities for collaboration with the international professional chemical community. The Department of State called on the National Academies to assist in the CSP's efforts to promote chemical safety and security in developing countries."--Publisher's description.